Simplify the given expression below: (4 + 2i) − (1 − 7i) 5 − 5i 5 + 9i 3 + 9i 3 − 5i

Answers

Answer 1
Answer: The best way to think of complex numbers is through x and y coordinates, if a number is just on its own (real) think of it as the x ordinate. Conversely if the number is say 2i (imaginary), just think of it as the y=2.
So 4+2i - (1-7i) = 4+2i-1+7i = (4-1) + i(2+7) = 3 +9i
That can be though of as (3,9). A complex number is just two separate real numbers, a real part and an imaginary part.
Answer 2
Answer:

The value of the complex expression will be 3 + 9i. Then the correct option is C.

What is a complex number?

The complex number is the combination of the real part and the imaginary part.

Then the complex number is given as

⇒ a+bi

The complex expression is given below.

⇒ (4 + 2i) and (1 − 7i)

Then the difference between the complex number will be

⇒ (4 + 2i) - (1 - 7i)

Simplify the complex expression, then the complex expression will be

⇒ (4 + 2i) - (1 - 7i)

⇒ 4 + 2i - 1 + 7i

⇒ 3 + 9i

The value of the complex expression will be 3 + 9i.

Then the correct option is C.

More about the complex number link is given below.

brainly.com/question/10251853

#SPJ5


Related Questions

What number is 40% of 200?
The formula for density is given by p=m/v where p is density, M is mass and V is volume. If a substance has a mass of 27.82 grams and a volume of 3.6 ml, what is the most accurate density of the substance in g/ml7.7 7.7278 7.73 0.1
Which shows the factored form of x2 – 12x – 45?(x + 3)(x – 15) (x – 3)(x – 15) (x + 3)(x + 15) (x – 3)(x + 15)
Help me with math ( 9th grade)
Make x the subject of m=n + x/p URGENT!! Please

Solve. Good luck! Please do not try to google this.(x^2+x-2)/(6x^2-3x) = √(2x) + (3x^2)/(2)

Answers

(x^(2) + x - 2)/(6x^(2) - 3x) = √(2x) + (3x^(2))/(2)
(x^(2) + 2x - x - 2)/(3x(x) - 3x(1)) = (2√(2x))/(2) + (3x^(2))/(2)
(x(x) + x(2) - 1(x) - 1(2))/(3x(x - 1)) = (2√(2x) + 3x^(2))/(2)
(x(x + 2) - 1(x + 2))/(3x(2x - 1)) = (2√(2x) + 3x^(2))/(2)
((x - 1)(x + 2))/(3x(2x - 1)) = (2√(2x) + 3x^(2))/(2)
((x - 1)(x + 2))/(3x(2x - 1)) = (2√(2x) + 3x^(2))/(2)
3x(2x - 1)(2√(2x) + 3x^(2)) = 2(x + 2)(x - 1)
3x(2x(2√(2x) + 3x^(2)) - 1(2√(2x) + 3x^(2)) = 2(x(x - 1) + 2(x - 1))
3x(2x(2√(2x)) + 2x(3x^(2)) - 1(2√(2x)) - 1(3x^(2))) = 2(x(x) - x(1) + 2(x) - 2(1)
3x(4x√(2x) + 6x^(3) - 2√(2x) - 3x^(2)) = 2(x^(2) - x + 2x - 2)
3x(4x√(2x) - 2√(2x) + 6x^(3) - 3x^(2)) = 2(x^(2) + x - 2)
3x(4x√(2x)) - 3x(2√(2x)) + 3x(6x^(3)) - 3x(3x^(2)) = 2(x^(2)) + 2(x) - 2(2)
12x^(2)√(2x) - 6x√(2x) + 18x^(4) - 9x^(3) = 2x^(2) + 2x - 4
12x^(2)√(2x) - 6x√(2x) = -18x^(4) + 9x^(3) + 2x^(2) + 2x - 4
6x√(2x)(2x) - 6x√(2x)(1) = -9x^(3)(2x) - 9x^(3)(-1) + 2(x^(2)) + 2(x) - 2(2)
6x√(2x)(2x - 1) = -9x^(3)(2x - 1) + 2(x^(2) + x - 2)

Final answer:

To solve the given equation, first simplify both sides. Factor the numerator and denominator on the left side, then solve the quadratic equation obtained.

Explanation:

To solve the given equation:

(x^2+x-2)/(6x^2-3x) = √(2x) + (3x^2)/(2)

First, we need to simplify both sides of the equation. By factoring the numerator and denominator of the left side, we get:

x+22x.

Next, we can simplify the equation further by multiplying both sides by 2x. Finally, we solve the quadratic equation obtained by moving all terms to one side:

2x+4.

Therefore, the solution to the given equation is x = -2.

Learn more about Solving Equations here:

brainly.com/question/17595716

#SPJ12

Find the distance between (11, 10) and (1,3). Round your answer to
the nearest tenth.

Answers

Answer:

              12.2

Step-by-step explanation:

d=√((x_2-x_1)^2+(y_2-y_1)^2)\n\nd=√((1-11)^2+(3-10)^2)=√((-10)^2+(-7)^2)=√(149)\n\nd=12.2065...\approx12.2

Clayton climbed down 50 meters. he climbed down in 10-meter intervals. in how many intervals did clayton make his climb?

Answers

Answer:

Clayton make his climb in 5 intervals.

Step-by-step explanation

Given: Clayton climbed down 50 meters.

1 interval = 10 meters down

The number of intervals = 50 divided by 10

= (50)/(10)

= 5 intervals

Therefore, Clayton make his climb in 5 intervals.

To figure this out, divide 50 metres by 10 metre intervals


50 metres ÷ 10 metre intervals = 5 intervals

What is the least common multiple of 5 and 2?

Answers

1 is the least common multiple

Solve 4^2x=7 by graphing

Answers

Answer:

0.702 is the solution of this function.

Step-by-step explanation:

We have

           4^(2x)=7\n\n4^(2x)-7=0

Let us plot y=4^(2x)-7 when y value of this function is zero then that is the solution of 4^(2x)=7

Refer the figure given, we have at x = 0.702 y value is zero that is 0.702 is the solution of this function.

         

I can't solve that by graphing but I'll try logarithms:
log(7)4 = 2x
log(7)/log(4) = 2x
1.403 = 2x
x = 0.702

Day and Night Kennel charges $20 per day plus a food fee of $15 to board a pet. Home Away From Home Kennel charges $30 per day plus a food fee of $5. Which system represents this real-world situation?

Answers

Let,

"p" represent the total cost to board the pet (food fee + charge per day included)
"d" represent the total number of days to board the pet

Now,
$$The equation to find how much Day and Night Kennel chargers :
$$ p\ =\ 20d+15

$$The equation to find how much Home Away From Home Kennel :
$$ p\ =\ 30d+5



Answer:

Answer is (B)!!

Step-by-step explanation:

These people that have the green check are such a waste of time...

UW